2022
DOI: 10.1111/jcpp.13620
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Do antibullying interventions reduce internalizing symptoms? A systematic review, meta‐analysis, and meta‐regression exploring intervention components, moderators, and mechanisms

Abstract: Background: Effective antibullying interventions may reduce the impact of bullying on young people's mental health. Nevertheless, little is known about their effectiveness in reducing internalizing symptoms such as anxiety or depression, and what factors may influence intervention effects. The aim of this systematic review, meta-analysis, and metaregression is to assess the effects of school-based antibullying interventions on children's and adolescent's internalizing symptoms. The secondary aims are to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 69 publications
1
10
0
1
Order By: Relevance
“…The progress of the phase (i.e., more eveningness) explained the relationship between adjustments of biological sleep patterns and the aggressor behavior associated with emotional dysregulation (Hagenauer et al, 2009; Hasan et al, 2022; Kubiszewski et al, 2014). On the one hand, these data are in line with the previous literature that confirms a uniformity of the behavior of bullies‐victims adolescents with sleep problems in various geographies and cultures (Arhin et al, 2019; Figueiredo et al, 2018; Guzman‐Holst et al, 2022; Hasan et al, 2022; Matsumoto et al, 2022; Wang et al, 2020); on the other hand, data indicated a different behavioral trend in gender.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The progress of the phase (i.e., more eveningness) explained the relationship between adjustments of biological sleep patterns and the aggressor behavior associated with emotional dysregulation (Hagenauer et al, 2009; Hasan et al, 2022; Kubiszewski et al, 2014). On the one hand, these data are in line with the previous literature that confirms a uniformity of the behavior of bullies‐victims adolescents with sleep problems in various geographies and cultures (Arhin et al, 2019; Figueiredo et al, 2018; Guzman‐Holst et al, 2022; Hasan et al, 2022; Matsumoto et al, 2022; Wang et al, 2020); on the other hand, data indicated a different behavioral trend in gender.…”
Section: Discussionsupporting
confidence: 89%
“…The analysis of the consequences is the main focus of research of aggressive bullying/cyberbullying behaviors, but the causes also need to be determined to further intervene with concrete effects on anti-bullying (Guzman-Holst et al, 2022). One of the interventions concerns the identification of sleep quality problems and the chronotype of the subjects.…”
Section: Relationship Between Adolescent Mental Health Sleep Quality ...mentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions may have a range of goals, for example, to reduce peer victimisation and bullying or to build feelings of school belonging. The mental health impacts of anti‐bullying interventions have been examined in a number of recent systematic reviews, most notably those led by Guzman‐Holst, Zaneva, Chessell, Creswell, and Bowes (2022) and Fraguas et al. (2021), both of which concluded that the small positive effects observed are likely to translate into meaningful population benefits.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…A systematic review and meta-analysis including 22 studies (58 091 participants) showed that antibullying interventions had a very small effect in decreasing overall internalizing symptoms, anxiety and depression [22]. The use of CBT 'was significantly associated with smaller effects on internalizing symptoms' compared with when CBT elements were not utilized [22].…”
Section: Antibullying Interventionsmentioning
confidence: 99%